The Effectiveness of Situational Language Teaching (SLT) Approach in Teaching Speaking for Islamic Junior High School - Hairori Sahrul Hafiz (International Journal Labs, 2023)
SLT approach is an approach that involves the systematic principles of selection (the procedure by which lexical and grammatical content were chosen), graduation (principles by which organization and sequencing of contents were determined), and presentation (technique used for presentation and practice of items in a course). The purposes of this research are to know whether situational language teaching approach effective in teaching speaking for the eighth graders of Islamic junior high school, and then the extent of the effectiveness of situational language teaching. The design is pre-experimental research. The sample is randomly selected as the experimental class of the eighth graders. The data are collected by administering pre-test and post-test to the students. t-test is used to analyze whether the alternative hypothesis is accepted or not. The statistical analysis shows mean of the class on pre-test is 16.43 and post-test is 20.47 by using t-test at the level of significance (a) 0.05, gotten r-test = 0.561 and t-test is bigger than t-table that is t-test = 5.691 > t-table = 2.045, meaning that there is a significant difference between the students’ achievement in speaking before and after SLT approach implemented. It then portrays SLT approach significantly effective in teaching speaking and SLT approach has positive correlation with students’ speaking skill at the level of believe 95%. It is suggested that SLT approach in teaching speaking is recommended for the English teachers, but SLT approach is better implemented in small class because teachers are easier in managing the class.